q-Powders: a quick test for screening retronasal olfactory disorders with tasteless powders - Pieniak, Michal; Oleszkiewicz, Anna; Klockow, Marie; Yoshino, Ayaho; Haehner, Antje; Hummel, Thomas (European archives of oto-rhino-laryngology, 2022)
Purpose To investigate the clinical utility of q-Powders—a retronasal identification screening test. Methods A total of 156 subjects (92 females, mean age: 54.5 years ± 17.3 years) completed a 3-item q-Powders retronasal identification test and a 16-items Sniffin’ Sticks orthonasal identification test. We analyzed whether the q-Powders test could differentiate between subjects with normosmia and subjects with an olfactory disorder. Results Our data indicated that subjects with an olfactory disorder scored lower in the q-Powders test than subjects with normosmia. The analyses revealed q-Powders test sensitivity of 84% and a test specificity of 64.9% with a score of 2 points taken as a cutoff for olfactory disorders. Conclusion The 3-item q-Powders retronasal test may be used for screening purposes in clinical research. Level of evidence 4